PENERAPAN SISTEM PEMBELIAN DALAM KAITANNYA DENGAN SISTEM PENGELUARAN KAS TERHADAP EFEKTIVITAS PENGENDALIAN INTERN (Studi Kasus pada PT. Bogor Raya Development) - ., Jeffry (STIE Binaniaga, 2012)
Purchase transactions generally can be grouped into two, namely the purchase of local and import purchases. Purchase is a purchase from a local supplier in the country, while the import is a purchase from suppliers abroad. In making a purchase of goods at each company, the system of purchase accounting required in the purchase transaction. If the system of purchase does not or not properly controlled, then the company will be instability in the running of day-to-day operations. Purchase system set up ways to do all that is required by the purchase of the company. This system starts from the needs of a goods purchased goods until received.Goal of this research is to evaluate the system of purchase in connection with cash expenditure on service company. Evaluation conducted to determine whether the system is implemented in the purchase of the company is already a minimum of opportunity for cheating to make the purchase, from the goods are required to be purchased with the goods received. In addition, the authors also evaluate how the procedure of cash to pay suppliers in the company can be and avoid cheating. Research conducted by the author is in the PT. Bogor Raya Development, located in Bogor. PT. Bogor Raya Development is a company that functions as a Property Services, Golf Club, Sports Club, and the Event Organizer and the Hotel & Resort.Results of research indicate that the internal control system to the purchase and expenditure of cash on PT. Bogor Raya Development has not been good enough, there are still opportunities to go on cheating the system. Opportunities do cheating can be seen from a company function of purchase with the function of the receipt. In addition, in the accounting and finance, there is waste that is done, print the document, namely the Bank Exit three copies, and two duplicate the same stored in the same department. This is a waste because it is required to print a form that does not cost cheapThe evaluation in this research shows there are some things that do not apply to the PT. Bogor Raya Development, the system does not run the procedure is not written so that sometimes can make employees who are confused whether to go in the responsibility or not. In addition, the supervision of the goods that came has not been effective because it does not separated function of purchase and receipt of goods. Supervision of goods in the warehouse also has not been effective because it held by employees of the purchase. Written procedures that will be easier for employees to know the duties and responsibilities, in addition to the cash expenditure on the system there is waste to form Bank Exit. Thus the internal control system of purchase and cash expenditures can run effectively.Keywords: system purchases, cash expenditures, and internal control